2012
DOI: 10.1016/j.ijheatmasstransfer.2011.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Droplet retention on an incline

Abstract: The present study seeks to understand and predict droplet retention on smooth hydrophobic surfaces. The droplet shape and the advancing and receding contact angles are experimentally measured as a function of droplet size under the action of a gravitational force at different inclination angles. The advancing and receding contact angles are correlated with static contact angle and Bond number. A Volume of Fluid -Continuous Surface Force model with varying contact angles along the triple contact line is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…The test surfaces used in the experiments are identical to those described in Annapragada et al [24]. The experimental setup consists of a movable tilt stage for mounting the test surfaces, along with a high-speed camera for imaging from the side.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test surfaces used in the experiments are identical to those described in Annapragada et al [24]. The experimental setup consists of a movable tilt stage for mounting the test surfaces, along with a high-speed camera for imaging from the side.…”
Section: Methodsmentioning
confidence: 99%
“…A pseudo-Lagrangian methodology, described below, is developed to reduce the domain size and hence the computational time. The VOF-CSF method itself is described in detail in Annapragada et al [24]. In the current model, volume fraction smoothing is used to reduce the spurious velocities at the interface associated with the VOF method [27,28].…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass source is then calculated from the energy source and the latent heat on a per volume basis (Eqs. (5) and (6)) and stored in a memory location for each cell. This approach of calculating mass source has been validated in the test cases studied by Akhtar and Kleis [1] and other works including that of Welch and Wilson [37].…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Splashing of the splats has a decisive effect on final shape of splats. Usually, increasing the substrate temperature [16,17] and thermal contact resistance [21][22][23][24][25] will suppress the splashing. Other studies also confirmed that increasing the Reynolds number and Weber number could promote splashing [4,[18][19][20]31].…”
Section: Introductionmentioning
confidence: 99%